Uses of digital interactive devices in trials for crimes against humanity - Virginia Vecchioli (Sortuz)
The article reflects on the use of digital immersive technologies on the judicial space as long as bodies, objects and scenarios of crimes can be created/recreated, digitized and incorporated into oral audiences as proof of massacres or genocides. From the description of the use of interactive digital devices that recreate extermination centers of the Argentine dictatorship in audiences for crimes against humanity, I will question the relationship between technological resources and the production policies of truth and plausibility that enables them to participate in the judicial stage. Taking social sciences as a starting point, it is expected to show the productivity and potential of these technological resources in the field of criminal persecution, contributing to the work of jurists and justice system operators.